Bleeding from a Small-Intestinal Ulcer Associated with Chronic Hepatitis C - Kamimura, Hiroteru (Am J Case Rep, 2018)
Patient: Male, 69 Final Diagnosis: Lymphoma Symptoms: Gastrointesinal haemorrhage Medication: — Clinical Procedure: — Specialty: Gastroenterology and Hepatology OBJECTIVE: Unusual clinical course BACKGROUND: Hepatitis C virus infection is probably the most common chronic viral infection and affects an estimated 180 million people worldwide. Extrahepatic manifestations are well recognized among patients with chronic HCV infection. CASE REPORT: We report a case of melena occurring in a 69-year-old Japanese man who had been diagnosed with CHC and who was treated with antiviral therapy. CONCLUSIONS: Finally, he was diagnosed with multiple small intestine ulcers in a short time. We herein report the case of HCV with rapidly developing small intestine ulcers.